Capturing Stereotypes: Developing a Scale to Explore U.S. College Students' Images of Science and Scientists. (2010) - Wyer, Mary; Schneider, Jennifer; Nassar-McMillan, Sylvia; Oliver-Hoyo, Maria
No abstract available